THE EFFECT OF SERVICE QUALITY, PRODUCT QUALITY AND PRICE PERCEPTION ON PURCHASE DECISIONS - Risa Wininda; Rodi Syafrizal; Nursaimatussaddiya (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of Service Quality, Product Quality, and Price Perception on Purchasing Decisions of consumers at Butik Liza Tebing Tinggi. The research employed a quantitative approach with a total of 96 respondents selected using incidental sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS 25. The results showed that partially, Service Quality and Product Quality had a significant effect on Purchasing Decisions, with significance values ​​of 0.046 and 0.010, respectively. However, Price Perception did not have a significant effect on Purchasing Decisions, with a significant value of 0.259. Simultaneously, the three variables (Service Quality, Product Quality, and Price Perception) have a significant influence on Purchasing Decisions, with an F-value of 30.079 and a significance level of 0.000. The adjusted R² value of 0.479 indicates that 47.9% of the variation in Purchasing Decisions can be explained by these three variables. These findings highlight the importance of improving service and product quality to influence consumer purchasing decisions, while price remains a relevant factor in a comprehensive marketing strategy.